Career Exploration at the Middle School Level: Barriers and Opportunities - Samantha Godbey; Howard R. D. Gordon (Middle Grades Review, 2019)
In this essay, we discuss issues related to the integration of career exploration in our nation’s middle schools. We discuss the theoretical and empirical basis for career exploration at the middle school level and identify selected barriers to its effective implementation, namely with regards to career advising and parent involvement. We also propose new directions for practice and research as we work to counteract these barriers.
Keywords: career exploration; career advising; middle school; parent involvement